Assessment of the flexural behavior of reinforced concrete beams strengthened with concrete jackets. (15th July 2018) - Alhadid, M. Monir A.; Youssef, Maged A.
Highlights: Flexural and deformation behaviors of continuous jacketed RC beams are examined. Non-linear material models and moment redistribution are considered in analysis. Modification factors to account for the influence of interfacial slip are proposed. Geometrical and mechanical properties are examined in view of a parametric study. Interfacial slip and shear stress distributions are evaluated in the analysis. Abstract: Analysis of continuous jacketed Reinforced Concrete (RC) beams requires accounting for the nonlinear behavior of the interface and the materials as well as redistribution of moments. This kind of analysis is complex and require an advanced level of knowledge and experience to perform. Engineers need simplified yet robust tools to practically predict the actual behavior of jacketed RC beams. In the current practice, slip is neglected in the analysis and monolithic behavior is assumed for the jacketed section, which result in higher estimates of stiffness and/or capacity. This paper provides a simplified method to analyze continuous jacketed RC beams taking into account the interfacial slip distribution and the actual nonlinear behavior of both concrete and steel. An iterative calculation algorithm is developed to determine the moment–curvature curves of a jacketed beam at different sections. The developed method allows the evaluation of interfacial slip and shear stress distributions in ductile reinforced concrete beams. The developed method is utilized to conduct an extensive parametric study, which resulted into modification factors that can be used to calculate the capacity and deformations of a strengthened beam considering the interfacial slip.